Self-Starting Harmonic Mode-Locked Thulium-Doped Fiber Laser with Carbon Nanotubes Saturable Absorber - Harun, Sulaiman Wadi; Saidin, N.; Zen, D.I.M.; Ali, N.M.; Ahmad, Harith; Ahmad, F.; Dimyati, K. (Institute of Physics, 2013)
We report a ring cavity passively harmonic mode-locked thulium-doped fiber laser (TDFL) using a newly developed single-wall carbon nanotube-based saturable absorber. The TDFL generates the 25th harmonic mode-locked stretched pulse train with a high repetition rate of 213 MHz and a pulse duration of 710 fs. The laser operates at 1901.6 nm with an average power of 1.89 mW, which corresponds to the pulse energy of 0.008 nJ, at 1552 nm pump power of 719 mW. The peak-to-background ratio is measured to be 60 dB, which indicates the stability of the laser.